The role of the cysteine-rich domain and netrin-like domain of secreted frizzled-related protein 4 in angiogenesis inhibition in vitro - Longman, D.; Arfuso, F.; Viola, H.; Hool, L.; Dharmarajan, Arunasalam (Cognizant Communication Corp., 2012)
Secreted frizzled-related protein 4 (sFRP4) is a Wnt signaling antagonist. Classically, sFRP4 antagonizes the canonical Wnt signaling pathway, resulting in decreased cellular proliferation and increased apoptosis. Recent research from our laboratory has established that sFRP4 inhibits angiogenesis by decreasing proliferation, migration, and tube formation of endothelial cells. The objective of this study was to examine the role of sFRP4’s cysteine-rich domain (CRD) and netrin-like domain (NLD) in angiogenesis inhibition. Experiments were carried out to examine cell death and tube formation of endothelial cells after treatment with the CRD and the NLD. The CRD was seen to inhibit tube formation of endothelial cells, which suggests that this domain is important to sFRP4’s antiangiogenesis property. In addition, the NLD promoted endothelial cell death and may also inhibit angiogenesis. Furthermore, treatment with the CRD and the NLD increased endothelial intracellular calcium levels. Our findings implicate a role for both the CRD and NLD in angiogenesis inhibition by sFRP4. It is suggestive of alternative antiangiogenic downstream targets of canonical Wnt signaling and a possible importance of the noncanonical Ca2+ Wnt signaling pathway in sFRP4-mediated angiogenesis inhibition.